The Effects of Peripheral Magnetic Stimulation on Improving Impairment and Functional Activity in Individuals with Stroke - Techataweesub, Sakaowrat; Khobkhun, Fuengfa (Journal of Thai Stroke Society, 2022)
Peripheral magnetic stimulation (PMS) is one of several novel non-invasive treatment of individuals with stroke, in terms of improving impairments and functional activities debilitated by brain dysfunction. Studies focusing on the effects of PMS have shown that impairments such as a decrease in muscle tone or muscle guarding have been restored. It has also been shown to be useful in the relieving of pain, increasing in muscle strength and improving the use of the upper and lower extremities function. In addition, PMS also assists in the promotion of improvement in gait and the activities associated with daily living in individuals with stroke. The purpose of this review was to identify the extent of the impact of the use of PMS in improving impairment and functional activities in individuals with stroke as well as to summarize the findings to date. Whatever the aim of the use of PMS the intensity and type of pulse need to be considered in relation to the needs of the patient status. It also needs to be recognized that the use of PMS is not appropriate in some stroke patients and the physiotherapist needs to screen all patients before applying this treatment.